(untitled) (Research, Society and Development, 2022)
The objective of the present study was to trace the profile of the aerobic power of adolescents practicing futsal. Participated in the study 23 male athletes who had regular practice of futsal, with a mean age of (15.8± 1.0 years) belonging to the under-17 category. The volunteers underwent anthropometric assessments and the Yo-yo recovery test level I, to determine the total distance covered (m), the peak speed reached in the test (Km/h) and the VO2máx in (ml/kg/min) to find the aerobic power. The results found in our study showed values of 690.2 m (± 176.7) for the total distance covered by the athletes at the end of the test, associated with a peak speed of 15.4 km/h (± 0.4) and an estimated VO2máx of 42.5 ml/kg/min (± 1.8). We can conclude that the data referring to the aerobic power profile expressed by the VO2máx found in this investigation are important for teachers, coaches and physical trainers when planning and prescribing training for young athletes of this sport.